1997
DOI: 10.1093/nar/25.1.28
|View full text |Cite
|
Sign up to set email alerts
|

MIPS: a database for protein sequences, homology data and yeast genome information

Abstract: The MIPS group (Martinsried Institute for Protein Sequences) at the Max-Planck-Institute for Biochemistry, Martinsried near Munich, Germany, collects, processes and distributes protein sequence data within the framework of the tripartite association of the PIR-International Protein Sequence Database (,). MIPS contributes nearly 50% of the data input to the PIR-International Protein Sequence Database. The database is distributed on CD-ROM together with PATCHX, an exhaustive supplement of unique, unverified prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
138
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(138 citation statements)
references
References 13 publications
0
138
0
Order By: Relevance
“…Annotation was added from SGD annotation tables (table release time (20,21), the General Repository for Interaction Datasets (GRID; release 1.0) (22), and the Yeast Protein Database (YPD; as of 06/09/03) (23). Based on known interaction annotation and the frequency of appearance in a reference dataset containing one representative experiment for every tagged open reading frame in this study (n ϭ 22), the data were then sorted into three tables: previously reported interactors retrieved in the experiment, potential new interacting proteins detected, and likely contaminants (see supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…Annotation was added from SGD annotation tables (table release time (20,21), the General Repository for Interaction Datasets (GRID; release 1.0) (22), and the Yeast Protein Database (YPD; as of 06/09/03) (23). Based on known interaction annotation and the frequency of appearance in a reference dataset containing one representative experiment for every tagged open reading frame in this study (n ϭ 22), the data were then sorted into three tables: previously reported interactors retrieved in the experiment, potential new interacting proteins detected, and likely contaminants (see supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…To identify further components of the pre-mRNA 39-end processing machinery, a screen for synthetic lethal mutations with the poly(A) polymerase temperaturesensitive allele pap1-7 was carried out (Fig+ 1A)+ Mutant strains that did not grow in the absence of the wild-type PAP1 gene were identified on plates containing 5-fluoroorotic acid [5-FOA; Figs+ 1B,C]+ We obtained 26 temperature-sensitive mutants+ For five of them, tetrad analysis demonstrated a genetic linkage between the temperature-and 5-FOA-sensitive phenotypes+ These mutations, termed lcp1 to lcp5, are not linked to the plasmid-borne pap1-7 allele and define five complementation groups (results not shown)+ lcp mutations were isolated by several outcrosses with the W303 wild-type strain (see Table 1)+ Extracts were prepared from each of the mutant strains and tested for pre-mRNA 39-end processing in vitro according to standard procedures (Minvielle-Sebastia et al+, 1994)+ We found that extracts from all five mutants processed a 32 P-labeled pre-mRNA substrate to an extent comparable to a wild-type extract, even at elevated temperature (Fig+ 2A; data not shown)+ These results suggested that the mutated genes were not coding for subunits of essential factors involved in mRNA 39-end formation+ Below, we describe the characterization of LCP5+ Wildtype LCP5 was cloned by complementation of the temperature-sensitive phenotype of its corresponding mutant+ Open reading frame YER127w (Mewes et al+, 1997) was sufficient to render the cells temperatureresistant+ The gene has been previously characterized by systematic Ty insertional analysis on chromosome V+ Ty insertion in YER127w resulted in severe growth defects on rich medium (Smith et al+, 1996)+ The protein has also been found to interact with Ngg1p in a two-hybrid screen (Martens et al+, 1996)+ Ngg1p acts as a transcriptional coactivator/repressor and is involved in acetylation of nucleosomal histones+ However, to the best of our knowledge no function has been assigned to YER127w so far+ LCP5 is a single copy gene+ It codes for a protein of 357 amino acids and has a calculated molecular mass of 40+8 kD+ The predicted polypeptide has a high content of charged residues (33% D ϩ E ϩ K ϩ R)+ Computational analysis detected a putative nuclear lo-FIGURE 1. Schematic representation of the synthetic lethal screen with pap1-7+ A: The starting strain, containing the PAP1 disruption, the wild-type PAP1 allele and the pap1-7 allele+ B: Genotype after UV mutagenesis in the presence of the wild-type PAP1 gene+ C: Resulting genotype after counterselection for the wild-type PAP1 gene on 5-FOA plates+ ϩ: interaction supporting cell viability+ Ϫ: aberrant interaction that fails to support cell viability+ LCP : wild-type allele before UV mutagenesis, lcp Ϫ : mutated allele after UV mutagenesis+ LEU2, ADE2, URA3: selectable marker genes+ calization signal (Dingwall & Laskey, 1991) and a potential coiled coil region (Fig+ 2B)+ The amino acid sequence of the protein shows similarities to a putative orthologue (accession No+ SWISS-PROT: Q09713) in Schizosaccharomyces pombe (26+3% identity), and to a CCAAT enhancer-binding-like protein of Caenorhabditis elegans (Wilson et al+, 1994)+…”
Section: Synthetic Lethal Screen Identifies a Gene With Unknown Functionmentioning
confidence: 94%
“…Curated pair-wise interactions from the literature and membership in protein complexes from MIPS [23] were used as the gold standard positive set in each case. Randomly chosen protein pairs formed the gold standard negative data set.…”
Section: Deng Et Al (Dg)mentioning
confidence: 99%